An Automatic High Efficient Method for Dish Concentrator Alignment. (24th July 2014) - Wang, Yong; Li, Song; Xu, Jinshan; Wang, Yijiang; Cheng, Xu; Gu, Changgui; Chen, Shengyong; Wan, Bin
Abstract : Alignment of dish concentrator is a key factor to the performance of solar energy system. We propose a new method for the alignment of faceted solar dish concentrator. The isosceles triangle configuration of facet's footholds determines a fixed relation between light spot displacements and foothold movements, which allows an automatic determination of the amount of adjustments. Tests on a 25 kW Stirling Energy System dish concentrator verify the feasibility, accuracy, and efficiency of our method.